2018
DOI: 10.20956/jrvi.v2i1.4386
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Proteus mirabilis as foodborne disease bacteria in carcass of broiler chickens (Gallus domesticus)

Abstract: Poor hygiene of traditional market often resulted in bacterial contamination of chicken meat including Proteus mirabilis which is also serve as a foodborne disease in human. Proteus mirabilis is pathogenic to humans because it can produces the urease which results in urinary tract infections (UTI). This research aimed to determine the presence of Proteus mirabilis bacteria in chicken meat sold in some traditional markets in the city of Makassar. The samples used in this study (24 samples) were obtained from 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…-On xylose-lysin decarboxylate agar media, Proteus mirabilis was isolated [15] . -On listeria selective base medium, Listeria monocytogenes was isolated [16] .…”
Section: Isolation Of Certain Non-spore Forming Pathogenic Bacteriamentioning
confidence: 99%
“…-On xylose-lysin decarboxylate agar media, Proteus mirabilis was isolated [15] . -On listeria selective base medium, Listeria monocytogenes was isolated [16] .…”
Section: Isolation Of Certain Non-spore Forming Pathogenic Bacteriamentioning
confidence: 99%
“…The contamination of meat products with Proteus refers to fecal contamination and may cause poisoning when consuming Proteus contaminated water and food (DrZewiecka 2016). Study conducted by Jamaluddin et al (2018) in Makassar city, Indonesia showed that 12.5% of chicken meat samples were contaminated with P. mirabilis. Atlantibacter hermannii is a rod-shaped Gram-negative bacteria.…”
Section: Morphological and Molecular Identification Bacterial Isolatesmentioning
confidence: 99%